Determination of Weed Seeds Mixed with Wheat Product in Diyarbakır - Fırat PALA; Hüsrev MENNAN; Fatih ÇIĞ; Halil DİLMEN (Türkiye Tarımsal Araştırmalar Dergisi, 2018)
This research was performed to determine the weed seeds that are mixed into the harvested wheat crop in Diyarbakir in 2017. For this purpose, 100 samples were taken from wheat products on 10 provinces wheat cultivated intensively. Collected specimens were passed through sieves (6-60 mesh) and the crude and inanimate material in them was taken and the remaining weed seeds were separated. Weed seeds were examined under the binocular microscope and species identification was carried out. It was determined that the ratio of weed seeds in the wheat mass harvested in Diyarbakır was 0.51%. These weed seeds identified are 28 different weed species from 8 different families. It was found that the most of these weeds belonged to the Poaceae family with 13 species. It was found that the most of these weeds belonged to members of the Poaceae family with 13 species. It had been determined that the most dense weeds were Avena fatua and Avena sterilis. As a result, the amount of impurities (weed seeds + inanimate substances) in the 50.000 g wheat sample taken was determined as 485.3 g by weight and the mixing ratio was 1.0%. The number of weed seeds was 633 and the weight of seeds was 10.96 grams. Thus, it can be estimated that about 8.544 tons of weed seeds and impurities are mixed in 845.105 tons wheat produced in Diyarbakir on 2.638.909 da land for the year 2016. The quality and quantity of impurities in wheat is one of the criteria affecting the quality of wheat. Since weeds are not worth milling, it is important that they are controlled effectively during wheat production, or weeding out weeds pre-grinding is important for food and public health.